PENEGAKAN HUKUM TERHADAP TINDAK PIDANA PERTAMBANGAN BATUAN NON LOGAM PADA TANAH HAK MILIK MASYARAKAT (Studi Pada Satreskrim Polres Kerinci) - Mai, Maizardi; Saputra, Ebit Bimas (Universitas Ekasakti, 2018)
The enforcement of mining law is done on the land of property rights is an interesting part for the scientific study, because on one side of law enforcement is a constitutional obligation to maintain the jurisdiction of the state law, on the other hand the land ownership is constitutional recognition or part of the form of state protection law against its citizens, or more specifically that one of the characteristics of a constitutional state is the protection of human rights. Ownership of land is a part of human rights, and even property rights to land can be communal. Based on the above description, the issues discussed in this research are: Firstly, how is law enforcement against the criminal act of non-metallic rock mining on community property rights in the area of ​​Kerinci Police . Secondly, what are the obstacles faced in law enforcement of non-metallic rock mining action on community property rights in Kerinci District Police and how to overcome these constraints.